Film Animasi “Kanca Cilik” Sebagai Intervensi dalam Perilaku Mencari Bantuan Kesehatan Jiwa Pada Usia Remaja - Lani Tiara Karlina Putri; Ahmad Guntur Alfianto; Rahmania Ramadhani (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: Post-adolescent mental health problems in Indonesia are currently experiencing an increase from 2013 to 2018. Efforts and forms of intervention that can be carried out are through increasing the behavior of seeking mental health assistance. Such efforts can be health promotion. Proper health promotion for adolescent with film media. the animated film